The spike protein of severe acute respiratory syndrome (SARS) is cleaved in virus infected Vero-E6 cells - WU, Xiao Dong (Cell Res, 2004)
Spike protein is one of the major structural proteins of severe acute respiratory syndrome-coronavirus. It is essential for the interaction of the virons with host cell receptors and subsequent fusion of the viral envelop with host cell membrane to allow infection. Some spike proteins of coronavirus, such as MHV, HCoV-OC43, AIBV and BcoV, are proteolytically cleaved into two subunits, S1 and S2. In contrast, TGV, FIPV and HCoV-229E are not. Many studies have shown that the cleavage of spike protein seriously affects its function. In order to investigate the maturation and proteolytic processing of the S protein of SARS CoV, we generated S1 and S2 subunit specific antibodies (Abs) as well as N, E and 3CL protein-specific Abs. Our results showed that the antibodies could efficiently and specifically bind to their corresponding proteins from E.coli expressed or lysate of SARS-CoV infected Vero-E6 cells by Western blot analysis. Furthermore, the anti-S1 and S2 Abs were proved to be capable of binding to SARS CoV under electron microscope observation. When S2 Ab was used to perform immune precipitation with lysate of SARS-CoV infected cells, a cleaved S2 fragment was detected with S2-specific mAb by Western blot analysis. The data demonstrated that the cleavage of S protein was observed in the lysate, indicating that proteolytic processing of S protein is present in host cells.